ANALISIS KERUSAKAN JALAN KESATRIAN AKMIL DENGAN METODE PCI (PAVEMENT CONDITIONAL INDEX) - Dicky Arif Priatama; Agung Prapsetyo; M. Zain Triputra; Budi Mawardi Syam (PPM Sdirjianbang Akademi Militer, 2023)
The Military Academy is an educational institution for the Army to educate prospective Army officers as Defense personnel based on local wisdom and can be recognized internationally in 2025. The condition of the roads in the knight environment was found to be damaged and on the other hand the road conditions were rehabilitated more than 10 years ago. One of the efforts that can be made to support Akmil as a center of excellence is the need to conduct research on the condition of the Military Academy Knights roads which can be used as a basis for improving road conditions in the Military Academy Knights. The research uses quantitative and qualitative methods by maximizing field observations and interviews for solutions related to damage to the research object. The results of the study show that the Pavement Conditional Index (PCI) method can show the condition of roads in the Military Academy by obtaining fair, good, very good, and excellent values ​​so that it can be determined how to maintain and deal with road damage in the Military Academy Knights